Education by inspiration - Paddock, Kate (My University, 1900)
Introduction: Nothing is more astonishing than what can be done by one person, yet how few compared with the many around us ever accomplish any thing at all. We need not restrict this to the building of some great city, or the overthrowing of an Empire; but we may also apply it to the making the best of our own lives and surroundings. The greater part of the world who would never take the trouble (and trouble is three fourths of power) to accomplish any thing themselves, are very anxious to prove that in the case of those who do accomplish, all was in their favor. On the contrary, history proves that the greatest minds and the most successful people were originally the most common place. Workers are beings in real power. Honor has been spoken of as only the shadow of which they have in their lives held the substance. It should be shown in school and public education that personality is in itself an influence and even a direct power, which held at its height, nothing can overthrow or resist. The indolent and cowardly are only too ready to say, “I can’t,” but of what good are ability and great power, if the will and the conscience do not open a channel for them. Great powers are to us a marvel and an inspiration; the more of an inspiration, the more they prove themselves natural and possible to human beings. One of the greatest victories over the tyranny of unpaid labor was won by the moral force of opinion; one might say by the cannon ball, but what was war but the resistance by the South of those forces which it saw could not help but abolish Slavery. Education by inspiration is not restricted to any age or any cause. It is the education which fits us for words and deeds by which more or fewer individuals may be benefited.
Citation: Paddock, Kate. Education by inspiration. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Education; Inspiration; Theses